2016
DOI: 10.3389/fnins.2016.00360
|View full text |Cite
|
Sign up to set email alerts
|

ERP Correlates of Simulated Purchase Decisions

Abstract: Decision making in economic context is an everyday activity but its neuronal correlates are poorly understood. The present study aimed at investigating the electrophysiological brain activity during simulated purchase decisions of technical products for a lower or higher price relative to a mean price estimated in a pilot study. Expectedly, participants mostly decided to buy a product when it was cheap and not to buy when it was expensive. However, in some trials they made counter-conformity decisions to buy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 65 publications
3
21
0
3
Order By: Relevance
“…This finding was later replicated by an independent research team (Goto et al, ). Moreover, Gajewski, Drizinsky, Zulch, & Falkenstein () reported an enhanced fronto‐central N200 during purchase decisions regarding overpriced and underpriced items. However, most research on this component has focused on cognitive mechanisms related to but different than valuation, such as cognitive control, attention, novelty or sequential matching (Folstein & Van Petten, ).…”
Section: Prominent Candidate Eeg Featuresmentioning
confidence: 99%
“…This finding was later replicated by an independent research team (Goto et al, ). Moreover, Gajewski, Drizinsky, Zulch, & Falkenstein () reported an enhanced fronto‐central N200 during purchase decisions regarding overpriced and underpriced items. However, most research on this component has focused on cognitive mechanisms related to but different than valuation, such as cognitive control, attention, novelty or sequential matching (Folstein & Van Petten, ).…”
Section: Prominent Candidate Eeg Featuresmentioning
confidence: 99%
“…Neural studies also provided neuroscientific evidence that the activities in distinct neural circuits correlated with specific product cues and review cues when choosing online products. [10][11][12] These studies indicated a trade-off process between product price and online rating in an online shopping context, which required consumers to think carefully before making decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Cuthbert et al ( 2000 ) in our study, when subjects had continuous win or continuous lose experiences, higher arousing emotion intensity had been elicited compared with single win or single lose experiences. Gajewski et al ( 2016 ) used facial expression as stimuli in their study to analyze the neural correlates of a simulated purchase decision task. However, no significant effects were found by facial expression upon participants' neural process.…”
Section: Discussionmentioning
confidence: 99%